Pathophysiology of polycystic ovary syndrome revisited: Current understanding and perspectives regarding future research - Harada, Miyuki (Reproductive medicine and biology, 2022)
Background Polycystic ovary syndrome (PCOS) is the most common endocrine disorder among reproductive‐age women and has lifelong effects on health. Methods In this review, I discuss the pathophysiology of PCOS. First, I summarize our current understanding of the etiology and pathology of PCOS, then, discuss details of two representative environmental factors involved in the pathogenesis of PCOS. Finally, I present perspectives regarding the directions of future research. Main findings The pathophysiology of PCOS is heterogeneous and shaped by the interaction of reproductive dysfunction and metabolic disorders. Hyperandrogenism and insulin resistance exacerbate one another during the development of PCOS, which is also affected by dysfunction of the hypothalamus‐pituitary‐ovarian axis. PCOS is a highly heritable disorder, and exposure to certain environmental factors causes individuals with predisposing genetic factors to develop PCOS. The environmental factors that drive the development of PCOS pathophysiology make a larger contribution than the genetic factors, and may include the intrauterine environment during the prenatal period, the follicular microenvironment, and lifestyle after birth. Conclusion On the basis of this current understanding, three areas are proposed to be subjects for future research, with the ultimate goals of developing therapeutic and preventive strategies and providing appropriate lifelong management, including preconception care. Three principal characteristics of the pathophysiology of PCOS have been identified to date: an interaction between reproductive dysfunction and metabolic disorders, high familial aggregation and heritability, and a substantial contribution of environmental factors. The following three areas represent targets for future research. 1) To identify the factors that induce the development and progression of PCOS after birth. 2) To elucidate the mechanisms underlying the high heritability of PCOS. 3) To identify biomarkers to that should be used to identify individuals at high risk during their early life. Future research should aim to develop therapeutic and preventive strategies, with the ultimate goal of achieving appropriate lifelong management, including preconception care.